Association Between Acupoint Selection, Target Symptoms, and Traditional Chinese Medicine Diagnosis in Real-Time Clinical Practice in a Comprehensive Cancer Center. (June 2020) - Liu, Wenli; Qdaisat, Aiham; Lopez, Gabriel; Narayanan, Santhosshi; Underwood, Susan; Spano, Michael; Reddy, Akhila; Guo, Ying; Yeung, Sai-Ching; Bruera, Eduardo; Cohen, Lorenzo
Background: Acupuncture intervention in actual practice is rarely reported and may be different from that applied in acupuncture research.Objectives: To review acupuncture practice in an integrative medicine clinic and characterize the association between targeted symptoms, traditional Chinese medicine (TCM) diagnosis, and acupoint selection.Methods: We reviewed outpatient acupuncture records from March 2016 to April 2018. Statistical analyses were applied to characterize referral symptoms and associated TCM diagnosis as well as acupoint selection.Results: The final analysis included 5393 acupuncture records (1264 patients). Twelve TCM diagnosis components were identified in the referral symptoms of pain, neuropathy, xerostomia, and hot flashes. Pain was associated with 78 different TCM diagnoses (combinations of TCM diagnosis components). Total of 217 different acupoints were used in the acupuncture treatments (1739) for neuropathy. The acupoint yintang was used in 73.8% of the visits for neuropathy, yet only in 26.5% ( P < .001) of the treatments when patients had a TCM diagnosis of qi deficiency, qi stagnation, and blood stagnation. Similarly, both consistencies and variations were seen in acupoint selection with each targeted symptom and its associated TCM diagnoses.Conclusions: TCM diagnosis was not homogeneous among acupuncture treatments for a single referral symptom. In contrast to most of the research on acupuncture for symptom control, there were considerable variations in acupoint selection among treatments for the same symptom in a clinical setting. Future research is needed to examine the clinical relevance of a fixed intervention structure in acupuncture research and the value of individualized acupuncture treatment.